INTEGRATING AI-ART TOOLS INTO FINE ARTS CURRICULA - BS, Hemalatha; Srivastava, Swati; Choudhary, Rama; Saini, Ramesh; Seth, Kanika; Mundada, Kapil (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The introduction of AI-art tools into the curriculum of the field of fine arts is a drastic deviation of the current art education process, as it alters how students perceive, experiment, and construct a work of visual art. As more and more generative algorithms, diffusion models, and interactive AI systems are made accessible, they offer novel forms of creativity through more traditional forms of media and processes. The paper explains how AI-art tools can be incorporated into the fine art course in an intellectual manner to enhance the creative inquiry, diversify visual problem solving, and interdisciplinary skills that will be used in the artistic used sectors in the future. In accordance with the sources related to the theme of digital art education and current tendencies in the field of creative technologies based on AI, the paper will provide the pedagogical premises of the curricular integration, the importance of shaping adaptability, critical thinking, and technological fluency in art students. It is proposed to use a hybrid creative process, and the design of a framework of integration, specific curriculum modules, studio practices, centered around AI processes and the workflow, and process evaluation in terms of AI processes and approaches. The framework does not claim that AI is going to replace the fundamental artistic abilities but, instead, it will act as an extension that will enable the individuals to discover more, develop quicker, and democratize numerous sophisticated creative means. The final product of the AI-enhanced art education may be positive with more developed imagery, cross-disciplinary interaction, and keeping up with the latest tendencies in the sphere.